MALNUTRISI PADA PASIEN PPOK - Pakpahan, Edwin Anto (Jurnal Kedokteran Methodist, 2022)
Objectives : Chronic obstructive pulmonary disease (COPD) is a non-communicable disease and is a global health problem. COPD is a disease characterized by progressive airflow limitation associated with chronic inflammation of the airways and lung parenchyma due to exposure to noxious gases or particles. Airflow limitation in COPD occurs due to changes in airway structure caused by parenchymal destruction and pulmonary fibrosis. Gastroesophageal Reflux Disease (GERD) is a chronic disease that occurs in adults. Factors that can cause GERD are eating patterns including certain types of food consumed, eating frequency, and eating irregularities. Malnutrition is a condition where the body does not get adequate nutritional intake. Malnutrition can also be called a condition caused by an imbalance between food intake and nutritional needs to maintain health Clinical Features : Patients have complaints; Cough, shortness of breath, decreased appetite, nausea and vomiting with every meal, weakness, dizziness, and weight loss Intervention and outcomes : COPD was given acetylcysteine ​​infusion, retaphyl, injection aminophylline 24 mg/ml, Gerd was given sucralfate syrup 100 ml, esomeprazole injection, and nutritional intervention; energy, protein: , carbohydrates, and fats. The results obtained by the patient experienced improvement with COPD, GERD and Nutrition Interventions. Conclusion:. From the results obtained in COPD patients, nutritional intervention is very important, especially high in protein and low in carbohydrates. Because high carbohydrates can trigger shortness of breath in patients. and it was proven that when the patient intervened at the hospital there was an improvement and when the patient came home he came back with complaints of shortness of breath and weakness.